A study: the volatility of exchange rate that could affect stock market in Malaysia / Nawwar Wan Mansoor - Wan Mansoor, Nawwar (Faculty of Business and Management, 2010)
This study examines the relationships between exchange rate and stock market in Malaysia and the relationships between exchange and stock market in Malaysia in different economic condition. Extending related empirical studies, comparative analyses of pre-crisis, crisis, and post crisis periods are conducted to comprehensively evaluate how the relationship between exchange rate and stock market in Malaysia was affected by financial crises. In general, the results show that there are positive relationships between exchange rate and stock market in Malaysia. In addition, exchange rate has no significant relationship on stock market in Malaysia at pre- economic crisis and during economic crisis. However, exchange rate has significant relationship with stock market generally for 5 years. In addition to this, exchange rates are one of the macroeconomic variables that will explain stock market in Malaysia. In this paper Regression Analysis approach was used to determine the significant relationship between exchange rate and stock market in Malaysia by way of analysing the trend of the exchange rate and stock markets for the period January 2005 to August 2010.Monthly data were used for the analysis.